2019
DOI: 10.1038/s41371-019-0255-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of chlorthalidone and hydrochlorothiazide—meta-analysis

Abstract: Hypertension is a complex syndrome of multiple hemodynamic, neuroendocrine, and metabolic abnormalities. The goals of treatment in hypertension are to optimally control high blood pressure and to reduce associated cardiovascular morbidity and mortality using the most suitable therapy available. Hydrochlorothiazide (HCTZ) and chlorthalidone (CTLD) are with proven hypertensive effects. The topic of our meta-analysis is to compare the efficacy of HCTZ and CTLD therapy in patient with hypertension. A search of ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 36 publications
0
19
0
3
Order By: Relevance
“…Recent pharmacoepidemiological studies showed a cumulative, dose-dependent association between hydrochlorothiazide (HCTZ), one of the most widely prescribed diuretic, antihypertensive drug, over the world [ 1 ], and increased nonmelanoma skin cancers (NMSCs) risk [ 2 , 3 ]. On these bases, the European Medicine Agency Pharmacovigilance Risk Assessment Committee, recommended to amend the Summary of Product Characteristics for HCTZ containing products with special warnings and precautions [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent pharmacoepidemiological studies showed a cumulative, dose-dependent association between hydrochlorothiazide (HCTZ), one of the most widely prescribed diuretic, antihypertensive drug, over the world [ 1 ], and increased nonmelanoma skin cancers (NMSCs) risk [ 2 , 3 ]. On these bases, the European Medicine Agency Pharmacovigilance Risk Assessment Committee, recommended to amend the Summary of Product Characteristics for HCTZ containing products with special warnings and precautions [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The modifiable contributing factors for IHD are hypertension, diabetes mellitus (DM), lipid imbalance, and cigarette smoking [ 5 ]. These can be classified under metabolic syndrome, which activates plaque formation, promotes thrombosis and inflammation, and increases the risk for cardiovascular disease development [ 6 ]. A range of debilitating conditions such as collagen deposition and elastin reduction regularly exist in older people, resulting in a poor prognosis of IHD with disabilities and impairment in quality of life, worsening their condition [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chlortalidone is a compound that is often used as a diuretic for diuretic therapy. This compound has been shown to have a therapeutic diuretic effect as an antihypertensive [2]. Chlortalidone contains not less than 98.00% and not more than 102.0% C 14 H 11 C 1 N 2 O 4 S, calculated based on the dried substance.…”
Section: Introductionmentioning
confidence: 99%